2021
DOI: 10.1039/d0cs01174f
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative dehydrogenation of light alkanes to olefins on metal-free catalysts

Abstract: Metal-free boron- and carbon-based catalysts for the oxidative dehydrogenation of light alkanes is reviewed from the preparation methods, characterization, catalytic performance and mechanistic issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 300 publications
2
90
2
Order By: Relevance
“…Metal oxide-based catalysts have been widely studied for ODHP reaction in the past decades, which still faced with a great challenge of low propylene selectivity due to the over oxidation reaction. [2,3,4] In recent years, the superior activity of h-BN in ODHP was demonstrated, [2,3,5] which inspired a wave for the research of boron-based ODHP catalysts. Meanwhile, the active origin and reaction mechanism of h-BN in ODHP have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal oxide-based catalysts have been widely studied for ODHP reaction in the past decades, which still faced with a great challenge of low propylene selectivity due to the over oxidation reaction. [2,3,4] In recent years, the superior activity of h-BN in ODHP was demonstrated, [2,3,5] which inspired a wave for the research of boron-based ODHP catalysts. Meanwhile, the active origin and reaction mechanism of h-BN in ODHP have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the commercially used direct dehydrogenation route, oxidative dehydrogenation of propane (ODHP) is a promising alternative with non‐equilibrium limitation and resistance to coke deposition. Metal oxide‐based catalysts have been widely studied for ODHP reaction in the past decades, which still faced with a great challenge of low propylene selectivity due to the over oxidation reaction [2,3,4] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boron nitride (BN), one of the antioxidative metal‐free materials, has been discovered as novel catalysts in the oxidative dehydrogenation of light alkanes. [ 12‐13 ] Possibly due to the low presence of defects in pure BN and the inherent differences in electronic and geometry aspects between alkylbenzene and light alkane molecules, [ 14 ] a low styrene formation rate is usually observed in ODH of ethylbenzene over BN. An efficient strategy to solve this problem is to fabricate hybrid catalysts with multi‐component showing specific functions.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Further research reported that the initial ODHP activity of BN was low and required an activation period to reach a stable performance, and that during the functionalization of the initial BN, nitrogen was gradually substituted by oxygen to form boron oxide species on the surface of the material. 12,13 Due to the inert nature of pure h-BN, the formed nascent functional groups (B–O–B and B–OH groups) at the edge were proposed to contribute to the catalytic performance in the ODHP reaction. 14,15 The molecular structures of the oxygen-functionalized phases appearing in hexagonal boron nitride (h-BN) and boron nitride nanotubes (BNNT) after performing ODHP catalytic tests were characterized by spectroscopy.…”
Section: Introductionmentioning
confidence: 99%